The Effectiveness of the Application of the Problem-Based Learning Model Assisted by EKTS Simulation on The Learning Outcomes of Electric Motor Installation of TITL Students Tomohon 1 Christian Vocational School - Rompas, Parabelem Tinno Dolf; Rapar, Jocke Jonathan; Poli, Bellavel; Batmetan, Johan Reimon (JR Education, 2025)
This study aims to see the improvement of student learning outcomes in the subject of applying EKTS (Electrical Control Techniques Simulator) software in the subject of Electric Motor Installation of class XI TITL SMKS Kristen 1 Tomohon. Electrical control techniques simulator is a simulator software that can be used to design electromechanical systems. This software provides various kinds of electromechanical systems that use relays, time relays, buttons, motors, switches, and various basic mechanical systems. This study seeks to make students' understanding of electric motor installation circuits more understandable and can be understood clearly so that there are no more doubts and fears when practicing them which can cause poor student learning outcomes. There are three circuits used in this study, namely the DOL (Direct On Line) circuit, Forward-Reverse and Star Delta circuits. From these three circuits, researchers can see the extent to which students' understanding of electric motor installations. This research will be conducted at SMKS Kristen 1 Tomohon. Which is addressed at Jl. Tomohon - Tondano No. 158, Matani Satu, Kec. Tomohon Tengah, Tomohon City, North Sulawesi Province. The current type of research uses experimental research, namely True Experimental research (pure experiment), namely experiments that follow procedures and meet the requirements of experiments, especially those related to controlling variables, control groups, providing treatment or manipulating activities and testing results. With the Two Group pretest-posttest design. The subjects of this study were students of class XI TITL II SMKS Kristen 1 Tomohon. The data obtained were analyzed using hypothesis testing. With this study, the average pre-test was 62.86 and the average post-test score was 82.86. The results of this study indicate an increase in learning outcomes for electric motor installation lessons in class XI TITL II SMKS Kristen 1 Tomohon.